Epidemiological profile of patients undergoing rhinoplasty in a hospital rehabilitation center - Fabiano Calixto Fortes Arruda; Paulo Gonçalves Junior; Pablo Rassi Florencio; Wilson Valadao; Thiago de Almeida Valle (Revista Brasileira de Cirurgia Plástica)
Introduction: Rhinoplasty is one of the most common plastic surgeries worldwide. The development of knowledge of the nose’s anatomy is one of the most refined teachings in plastic surgery. In addition to dedication and studies, it requires visual technical experience for an adequate understanding of structures and ligaments. This study aims to describe the epidemiological profile of patients undergoing rhinoplasty in a tertiary hospital. Methods: Patients who underwent rhinoplasty at the Plastic Surgery Service of the Centro de Reabilitação e Readaptação Dr. Henrique Santillo (CRER), from January 2013 to December 2019, were studied in patients from the single health system. Results: 179 patients were studied, the majority of whom were female, with a mean age of 35 years, as the leading cause of trauma, the majority being primary rhinoplasty using an open technique. Conclusion: The patients’ profile is female, with a mean age of 35 years, mainly due to nasal deformity after trauma, with open primary surgery approach and cartilage grafts are common.